1986
DOI: 10.1051/jphyscol:19868224
|View full text |Cite
|
Sign up to set email alerts
|

Exafs Study of Active Intermediates : Heme Enzymes and Model Compounds

Abstract: The iron coordination structures of the oxygenated cytochrome P-450-CAM and chloroperoxidase and of a number of penta- and hexa-coordinate ferrous porphyrin complexes containing biologically relevant, sulfur axial ligands have been investigatied by EXAFS spectroscopy. The two oxygenated enzymes have both been found to contain a sulfur atom located 2.37 Å from the central heme iron. In the CO-ligated series of model complexes, two distinct categories of Fe-Sax distances have been observed that correlate with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Inasmuch as frozen dilute aqueous solutions have been generally established as the best (most functionally relevant) form of metalloproteins for structural study via the XAFS technique, the significantly longer iron-sulfur bond length for the frozen solution was somewhat unexpected. Kau et al (1986) also used XAFS to probe the iron coordination structures in a number of ferrous porphyrin complexes containing biologically relevant sulfur donor axial ligands. Their model for the iron-methionine axial ligation provides an iron-sulfur bond length of 2.41 Å, also longer than that indicated in the NMR solution structure.…”
Section: Figurementioning
confidence: 99%
“…Inasmuch as frozen dilute aqueous solutions have been generally established as the best (most functionally relevant) form of metalloproteins for structural study via the XAFS technique, the significantly longer iron-sulfur bond length for the frozen solution was somewhat unexpected. Kau et al (1986) also used XAFS to probe the iron coordination structures in a number of ferrous porphyrin complexes containing biologically relevant sulfur donor axial ligands. Their model for the iron-methionine axial ligation provides an iron-sulfur bond length of 2.41 Å, also longer than that indicated in the NMR solution structure.…”
Section: Figurementioning
confidence: 99%
“…Dawson, Hodgson, and their co-workers studied both low-spin ferric P-450-CAM and purified liver microsomal P-450. 54,55,[83][84][85][86] The EXAFS technique87-89 is particularly good at distinguishing sulfur donor ligands from nitrogen or oxygen donors and, with good data, is capable of determining metal-ligand bond distances to an accuracy of ±0.02 A. Although no geometrical information can be directly obtained from the EXAFS data, extensive crystallographic studies of ferric heme iron model complexes revealed that the Fe-N (porphyrin) distance can be used to distinguish six-coordinate from five-coordinate structures.90 Consequently, determination of the Fe-N (prophyrin) distance from analysis of the EXAFS data can indirectly provide information about the coordination number and, therefore, about the geometry.…”
Section: Low-spin Ferric Statesmentioning
confidence: 99%
“…2a) show the formation of a minor peak at 8983 eV, which has a higher intensity than that in the spectra of Wacker-equilibrated Pd1Cu5-Y. This indicates the formation of more Cu(I) species 13 in the catalyst with higher palladium loading after 4 hours under Wacker conditions. EXAFS analyses (Fig.…”
mentioning
confidence: 88%
“…The Cu and Pd K-edge XANES spectra of both as-prepared Pd1Cu5-Y and Pd4Cu5-Y indicate that copper is present as hydrated Cu(II) ( Fig. 2a: pre-edge feature at 8977.5 eV resulting from the 1s -3d transition; 13 continuum resonance peak at 8996 eV) and palladium as amminated Pd(II) ; Fig. S2, ESI †: weak IR band at 1310 cm À1 attributed to symmetric N-H deformation 9 ).…”
mentioning
confidence: 99%